NATIONAL LANGUAGE AND LITERARY VARIANT - Abdulazizova Sevara Ganiyevna; Axmadjonova Oydinoy; No'monjonova Gulnoza (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This article explores the relationship between the national language and its literary variant, focusing on their roles in cultural identity, education, and national unity. While the national language represents the broader linguistic identity of a nation, the literary variant serves as its standardized and formal expression. The article highlights the distinctions and interdependence of these two forms and emphasizes the importance of promoting the literary variant in education, media, and public life. Challenges related to globalization and the influence of foreign languages are also discussed, along with suggestions for preserving linguistic heritage.